The effect of wheel and nozzle diameter ratio on the performance of a Turgo turbine with pico scale - Budiarso; Dwijaya Febriansyah; Warjito; Dendy Adanta (Energy Reports, 2020)
A Turgo turbine with a pico scale (<5 kW) is one solution to supplying electrical energy in remote areas because of its low construction costs and ease of maintenance. Based on empirical equations, the ratio of the wheel (D) and nozzle diameter (d), or D/d, of a Turgo turbine must be determined precisely because it affects wheel velocity, which has an impact on performance and/or efficiency. However, the optimum D/d ratio has not yet been clearly determined. To find the optimum D/d ratio for a Turgo turbine with a pico scale that can produce maximum electrical power, this study will examine five variations of the D/d ratio: 11.6, 13.8, 14.7, 22 and 27.5. In order for this turbine to be implemented in remote areas, coconut shell is proposed as the material for its blades. The results of the analysis, which used a one-way analysis of variance (ANOVA) test with a confidence level of 92.5%, show that the D/d ratio had a significant influence on performance. Based on the results, aD/d ratio of 22 produces the highest efficiency - 34.97% with an electric power of 5.34 W (13.21 Vdc ± 0.1 Vdc and 396.4~mA ± 7.46~mA) - compared to the other ratios. Thus, the pico-scale Turgo turbine runner design is optimized at the D/d ratio of 22. Furthermore, coconut shell blades can be implemented for a pico-scale Turgo turbine.
Keywords: 330; Nozzle; Pico hydro; Remote areas; Turgo turbine; Wheel